2012
DOI: 10.1186/1475-2859-11-125
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rhizobium endoglucanase CelC2 in cellulose biosynthesis and biofilm formation on plant roots and abiotic surfaces

Abstract: BackgroundThe synthesis of cellulose is among the most important but poorly understood biochemical processes, especially in bacteria, due to its complexity and high degree of regulation. In this study, we analyzed both the production of cellulose by all known members of the Rhizobiaceae and the diversity of Rhizobium celABC operon predicted to be involved in cellulose biosynthesis. We also investigated the involvement in cellulose production and biofilm formation of celC gene encoding an endoglucanase (CelC2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 54 publications
3
70
0
2
Order By: Relevance
“…This behavior may result from a homeostasis strategy to regulate the proteins/enzymes levels required for cellular maintenance [57]. Figure 6 also shows a distinct difference between gene expressions on derivatized cellulose surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior may result from a homeostasis strategy to regulate the proteins/enzymes levels required for cellular maintenance [57]. Figure 6 also shows a distinct difference between gene expressions on derivatized cellulose surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the production of cellulose is important for biofilm formation 46, 47 . All selected strains are capable of producing cellulose, which will probably aid colonization of plant roots.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation was determined in flat-bottom polystyrene 96-well plates (Greiner) in 30% MM, in triplicates, as previously described (40). A preculture in the same medium was diluted to an OD 600 of 0.2, with a final volume 100 l, and grown without shaking for 48 h at 30°C.…”
Section: Methodsmentioning
confidence: 99%